2007
DOI: 10.1111/j.0030-1299.2007.16016.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic tradeoffs between egg number and egg size in three parasitic anisakid nematodes

Abstract: Phenotypic tradeoffs between number and size of eggs were tested in three component populations of three marine anisakid nematodes: Anisakis simplex , Pseudoterranova decipiens and Contracaecum osculatum . Body and uterine volumes (as proxies of female size), and egg number, mean egg volume and clutch volume (as descriptors of reproductive output) were measured in 50 females of each species. Evidence of a phenotypic tradeoff was detected only in A. simplex ; the first time that has been found in a parasite pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Studies on the presence of nematodes in Baltic Sea seals (H. grypus, P. vitulina and P. hispida) reported that each seal was infected with Anisakidae nematodes, with one grey seal showing an intensity of infection of up to 590 nematodes [59]. It is worth emphasizing that C. osculatum and P. decipiens females are very productive: one female P. decipiens produces on average about 60,000 eggs, while a female C. osculatum produces on average about 9,000 eggs [60]. If we multiply the number of grey seals by the number of nematodes in each seal and by the number of eggs that might be produced by each mature female parasite, we end up with a extremely high load of nematodes shed into the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the presence of nematodes in Baltic Sea seals (H. grypus, P. vitulina and P. hispida) reported that each seal was infected with Anisakidae nematodes, with one grey seal showing an intensity of infection of up to 590 nematodes [59]. It is worth emphasizing that C. osculatum and P. decipiens females are very productive: one female P. decipiens produces on average about 60,000 eggs, while a female C. osculatum produces on average about 9,000 eggs [60]. If we multiply the number of grey seals by the number of nematodes in each seal and by the number of eggs that might be produced by each mature female parasite, we end up with a extremely high load of nematodes shed into the environment.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, long-lived nematodes tend to achieve larger sizes and extended reproductive periods, especially in iteroparous species. Larger adult sizes are associated with increased reproductive capacity, such as higher egg production [54,55]. Additionally, larger adults have greater access to food, occupy better places to live as parasites, and have more reproductive opportunities compared to smaller ones [53].…”
Section: Plos Onementioning
confidence: 99%